2007
DOI: 10.1074/jbc.m705120200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tryptophan Hydroxylase-2 Gene Expression by a Bipartite RE-1 Silencer of Transcription/Neuron restrictive Silencing Factor (REST/NRSF) Binding Motif

Abstract: Tryptophan hydroxylase-2 (TPH2) is the rate-limiting enzyme in raphe serotonin biosynthesis, and polymorphisms of TPH2 are implicated in vulnerability to psychiatric disorders. Dynamic transcription regulation of TPH2 may underlie differences in vulnerability. We identified a transcription element in the TPH2 promoter that resembles the binding motif for RE-1 silencer of transcription (REST; also known as NRSF) transcription factor. REST limits tissue expression of non-neuronal genes through a canonical 21-bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…In the present study, the segment +8 to +53 of the TPH2 5′-UTR decreased luciferase activity and mRNA level strikingly, yet had a negligible effect on mRNA stability, suggesting that transcriptional mechanisms may be involved in the repression of gene expression by this region and that negative cis-element(s) should exist in this region. In accordance with these findings, a bipartite REST/NRSF binding motif that mediates transcriptional repression was recently identified in TPH2 5′-UTR between +9 to +35 (Patel et al 2007), just within the suppressive region (+8 to +53) revealed by our present study. In addition, our current preliminary data indicates that additional TF binding motifs in this region might also contribute to the transcriptional suppression of gene expression (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, the segment +8 to +53 of the TPH2 5′-UTR decreased luciferase activity and mRNA level strikingly, yet had a negligible effect on mRNA stability, suggesting that transcriptional mechanisms may be involved in the repression of gene expression by this region and that negative cis-element(s) should exist in this region. In accordance with these findings, a bipartite REST/NRSF binding motif that mediates transcriptional repression was recently identified in TPH2 5′-UTR between +9 to +35 (Patel et al 2007), just within the suppressive region (+8 to +53) revealed by our present study. In addition, our current preliminary data indicates that additional TF binding motifs in this region might also contribute to the transcriptional suppression of gene expression (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…1b, the proximal 5′ regulatory region (especially the inhibitory segment +8 to +53) shares a high homology between human, macaca and mouse TPH2. Putative TF binding sites for NEUROD1 (Beta-2/E47 dimer), Brn-2, and CEBP (CCAAT enhancer binding protein) were predicted in the core promoter, while the inhibitory region (+8 ∼ +53) contains putative sites for three TFs (NRSF, IA-1 and Myf-3), among which NRSF has been recently identified to confer transcriptional repression of TPH2 gene expression (Patel et al 2007), while IA-1 can also function as a transcriptional repressor (Breslin et al 2002). There are also several putative TF binding sites spanning or neighboring the 90A/G SNP, including two STRE (stressresponse element) sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms that control TPH2 expression are not fully understood, several reports suggest that the neuron-restrictive silencer factor, which recruits corepressor complexes containing HDAC1/2 [18], negatively regulates TPH2 expression [19]. Consistent with these reports, the increase in TPH2 expression was accompanied by hyper-acetylation of histone H3 at the promoter region of the TPH2 gene in the raphe slice cultures.…”
Section: Discussionmentioning
confidence: 73%
“…An unexplored mechanism involves repressor element silencing transcription factor/neuron-restrictive silencing factor (REST/NRSF). REST is a repressor of transcription of TPH2 (Patel et al, 2007) and CRF (Seth and Majzoub, 2001). Hence, it is present in serotonin neurons.…”
Section: Discussionmentioning
confidence: 99%